2010
DOI: 10.1103/physrevb.81.245420
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-induced band-gap opening in graphene superlattices

Abstract: We study n ϫ n honeycomb superlattices of defects in graphene. The considered defects are missing p z orbitals and can be realized by either introducing C atom vacancies or chemically binding simple atomic species at the given sites. Using symmetry arguments and electronic-structure calculations we show that it is possible to open a band gap without breaking graphene point symmetry. This has the advantage that new Dirac cones appear right close to the gapped region. We find that the induced gaps have an approx… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 49 publications
5
89
1
1
Order By: Relevance
“…The different behavior of these two classes (multiples of 3 or not of the primitive cell of the pristine system) of graphene superlattices is now wellunderstood in terms of the energy band-folding model. [55][56][57] Indeed, even in pure graphene, when p is a multiple of 3, the two Dirac points K and K ′ in the primitive cell are folded to the Γ point of the hexagonal first-Brillouin zone (BZ) of the superlattice, giving rise to a fourfold degeneracy that can be broken, opening a band gap, by a periodic arrangement of defects. In the other case, the twofold degenerate Dirac points do not fold into Γ and a band gap opening can be induced by breaking the inversion symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…The different behavior of these two classes (multiples of 3 or not of the primitive cell of the pristine system) of graphene superlattices is now wellunderstood in terms of the energy band-folding model. [55][56][57] Indeed, even in pure graphene, when p is a multiple of 3, the two Dirac points K and K ′ in the primitive cell are folded to the Γ point of the hexagonal first-Brillouin zone (BZ) of the superlattice, giving rise to a fourfold degeneracy that can be broken, opening a band gap, by a periodic arrangement of defects. In the other case, the twofold degenerate Dirac points do not fold into Γ and a band gap opening can be induced by breaking the inversion symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…This case demonstrates the crucial role played by the intrinsic symmetry of the pattern in determining the electronic structure. [11][12][13] Let us now take a closer look at the triangular patterns of adatom groups that have hexagonal symmetry. In Fig.…”
Section: Adatom Patterned Graphene Nanomeshesmentioning
confidence: 99%
“…9,10 Using symmetry arguments and tight binding calculations, it was shown that the periodic structure of defects (such as B and N impurities) on graphene can exhibit semimetallic and semiconductor behavior. 11 Moreover, a weak perturbation potential forming a large hexagonal lattice in a two-dimensional (2D) electron gas was shown to lead to a massless Dirac fermion Hamiltonian with linearly crossing bands at Dirac points. [12][13][14] The majority of the current studies on graphene is devoted to its chemical modification to create derivatives with different structures and properties.…”
Section: Introductionmentioning
confidence: 99%
“…By looking at the total values of the direct piezoelectric constant, it is seen that for small dopant concentrations the common asymptotic value of approximately 5×10 −10 C/m is reached for all systems, 21 Let us just briefly recall that this is due to the fact that the band gap of the system varies with defect concentration according to two distinct behaviors depending on whether the considered superlattice is or not a multiple of 3 of the primitive cell of pristine graphene, as predicted by the energy band-folding model. [52][53][54] As a further consideration, we might notice that the vibrational contribution is always smaller in absolute value than the electronic one, which is found to dominate the in-plane piezoelectric response of functionalized graphene.…”
Section: In-plane Piezoelectricitymentioning
confidence: 99%